Hard cross-linked acrylic copolymer, adhesive and preparation method of hard cross-linked acrylic copolymer
The hard crosslinked acrylic copolymer is prepared by RAFT active polymerization, which solves the problem that existing adhesives are prone to deterioration in high temperature and high humidity environments, achieves higher high temperature resistance and wettability, and reduces the occurrence of residual glue and gelation problems.
Patent Information
- Application Number
- CN202411790781.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-08
AI Technical Summary
The existing adhesives are prone to deterioration in high temperature and high humidity environments, resulting in degradation of LCD screen display performance and poor wetting on the surface of polarizers, which makes it easy to cause residual glue problems.
Hard crosslinked acrylic copolymers were prepared by RAFT active polymerization, hard crosslinking and intermolecular force were constructed by bisacrylamide monomers to enhance the cohesion of the copolymers, and wettability was improved using acrylic ester monomers with low glass transition temperature.
It significantly improves the high temperature resistance and wettability of the adhesive, reduces the occurrence of residual glue problems, and avoids the occurrence of gelation problems.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_9
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, in particular to a hard cross-linked acrylic copolymer, an adhesive and a preparation method thereof. Background Art
[0002] With the widespread use of liquid crystal displays (LCDs) in automotive displays, televisions, desktop computers, mobile phones and other devices, certain severe environmental conditions (such as high and low temperatures, high humidity) have brought new challenges to screen displays. LCDs are usually composed of glass substrates, liquid crystal materials, polarizers, color filters and other components, and the polarizers are laminated to the glass substrate through an adhesive layer. Therefore, the adhesive layer is also facing the test of degradation conditions.
[0003] The adhesive layer is usually composed of adhesive components (acrylic copolymers, hardeners, silane coupling agents, etc.). Because acrylic copolymers need to have a certain degree of viscosity to tightly attach the polarizer to the glass substrate, some monomers with a low glass transition temperature (Tg) (such as butyl acrylate, -50°C) are often introduced in the process of synthesizing such polymers to ensure viscosity, which in turn sacrifices part of the high temperature resistance of the polymer.
[0004] In order to improve the heat resistance of polymers, a Chinese patent with publication number CN110423303A discloses an oil-soluble low-temperature internally cross-linked functional polyacrylate polymer and its application. The composition is composed of component A, component B and component C in a weight ratio of 1:2:2 and the content is adjusted to 45% to 55%. The component A is composed of polyacrylate with a polymerization reaction temperature of -25°C to -15°C. The composition and mass percentage of the polyacrylate are as follows: 20% to 60% of acrylic soft monomers and 5% to 20% of acrylic hard monomers. The invention introduces functional monomers (such as hydroxybutyl acrylate and hydroxyethyl acrylate) and reacts with hardeners (such as toluene diisocyanate) to form a cross-linked network and improve the stability of the polymer at high temperatures. The disadvantage is that the hardener is highly active and gelation problems are prone to occur during use.
[0005] In addition, the existing invention also improves the high temperature tolerance of the polymer by introducing a large amount of alkyl acrylate with a higher Tg (such as methyl acrylate, 8°C). The disadvantage is that the wettability of the polymer on the surface of the polarizer is poor, and residual glue is likely to occur during the rework process.
[0006] In order to solve the above problems, the present invention provides a hard cross-linked acrylic copolymer, an adhesive and a preparation method thereof. Summary of the invention
[0007] The object of the present invention is to provide a hard cross-linked acrylic copolymer, an adhesive and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a hard cross-linked acrylic copolymer, wherein the acrylic copolymer has a weight average molecular weight Mw of 100 to 150w and a polydispersity index PDI of 1 to 4;
[0009] Including acrylate monomers, bisacrylamide monomers, initiators, chain transfer agents and solvents;
[0010] When the total weight of the acrylic acid ester monomer and the bisacrylamide monomer is 100 parts, the acrylic acid ester monomer accounts for 80 to 99 parts, and the bisacrylamide monomer accounts for 1 to 20 parts.
[0011] More optimally, the acrylic acid ester monomer includes at least one of n-butyl acrylate, isobutyl acrylate, n-hexyl acrylate, n-octyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, n-nonyl acrylate, methoxyethyl acrylate, ethoxyethyl acrylate, isooctyl methacrylate, isodecyl methacrylate, lauryl methacrylate and tetradecyl methacrylate.
[0012] More optimally, the bisacrylamide monomer includes at least one of methylene bisacrylamide, ethylenediamine bisacrylamide, propylenediamine bisacrylamide and butanediamine bisacrylamide.
[0013] More optimally, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, dodecyl peroxide, tert-butyl perbenzoate and tert-butyl pervalerate; the initiator is used in an amount of 0.01 to 2 parts by weight.
[0014] More optimally, the chain transfer agent is selected from at least one of tert-butylbenzocarbodisulfate, carbazole-9-dithiobenzyl ester, 3-benzylsulfonylcarbonylthiosulfonylpropionic acid, 2-phenylethylbenzenedithiol ester, and 2-phenyl-2-propylbenzodisulfide; the chain transfer agent is used in an amount of 0.04 to 8 parts by weight.
[0015] More preferably, the solvent is ethyl acetate, toluene, methyl acetate or acetone.
[0016] A hard cross-linked acrylic adhesive is composed of an acrylic copolymer and a silane coupling agent, wherein the acrylic copolymer uses any one of the hard cross-linked acrylic copolymers mentioned above; and based on weight components, the silane coupling agent is used in an amount of 0.01 to 1 part relative to 100 parts of the acrylic copolymer.
[0017] More optimally, the silane coupling agent is selected from at least one of 3-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane, phenyltrimethoxysilane and vinyltriacetoxysilane.
[0018] A method for preparing a hard cross-linked acrylic adhesive, used for preparing the above-mentioned hard cross-linked acrylic adhesive, comprises the following steps:
[0019] S1, preparation of mixed monomer: taking a certain amount of acrylic acid ester monomer and bisacrylamide monomer and mixing them evenly to obtain a mixed monomer;
[0020] S2, preparation of acrylic copolymer: under nitrogen protection, add the mixed monomer, chain transfer agent and solvent in the formula amount into the reactor and heat to 65-70° C., add 1 / 3 of the initiator in the formula amount, initiate the reaction and keep warm for 2-3 hours; add 1 / 3 of the initiator and keep warm for 2-3 hours; finally add the remaining 1 / 3 of the initiator, keep warm for 2-3 hours, add the solvent, cool and discharge, and obtain acrylic copolymer;
[0021] S3, preparation of adhesive and polarizer element: take acrylic copolymer and silane coupling agent, add solvent to adjust viscosity, apply them on plastic film, and the coating thickness is 10-50μm; after coating, use 75℃-85℃ hot air to dry for 3-5min, stick it on polarizer, and mature it at 23℃ / 50% environment for 7 days to obtain the finished polarizer element.
[0022] More optimally, the coating method is a gravure coater, a blade coater or a rotary coater; the plastic film is a polyethylene terephthalate film that has been peeled off and has a thickness of 10 to 100 μm.
[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0024] (1) In the present invention, a high temperature resistant acrylic copolymer with a three-dimensional network structure can be prepared by RAFT active polymerization without using a curing agent.
[0025] (2) In the present invention, the hard crosslinks constructed by bisacrylamide monomers and the soft crosslinks constructed by intermolecular forces can significantly improve the cohesive force of the copolymer.
[0026] (3) In the present invention, the acrylic ester monomer used has a low glass transition temperature (Tg<-35°C) and has good wettability and adhesion to the polarizer substrate.
[0027] (4) The weight average molecular weight of the acrylic copolymer prepared by the present invention is 100-150w and has a narrow distribution, which can allow the adhesive layer to maintain sufficient viscoelasticity at a higher temperature and play a buffering role on the shrinkage stress generated by the polarizer. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] The present invention provides a hard cross-linked acrylic adhesive, and the specific preparation method is as follows:
[0030] S1. Preparation of mixed monomers.
[0031] The acrylic acid ester monomer and the bisacrylamide monomer in the formula amount are uniformly mixed to obtain a mixed monomer.
[0032] S2. Preparation of acrylic copolymer.
[0033] Under nitrogen protection, add the formula amount of mixed monomers, the above chain transfer agent and solvent into the reactor and heat to 65-70°C, add 1 / 3 of the formula amount of initiator, initiate the reaction and keep warm for 2-3 hours; add 1 / 3 of the initiator and keep warm for 2-3 hours. Finally, add the remaining 1 / 3 of the initiator, keep warm for 2-3 hours, add the solvent, cool and discharge, and obtain an acrylic copolymer;
[0034] The adhesive composition of the present invention is mainly composed of an acrylic copolymer (A) and a silane coupling agent (B). When coating, a solvent is often needed to adjust the viscosity, such as ethyl acetate, toluene, methyl acetate and acetone. There is no special restriction on the coating method, and gravure coater, blade coater and spin coater can be listed. The coating substrate is usually a plastic film, such as a polyethylene terephthalate film after peeling treatment. There is no special restriction on the thickness, and 10μm to 100μm is recommended. There is no special restriction on the drying method, usually hot air drying at 75℃-85℃ for 3-5min; the thickness of the adhesive layer is recommended to be 10μm to 50μm. The plastic film with the adhesive layer is attached to the polarizer and aged for 7 days at 23℃ / 50% environment conditions to obtain a polarizer element with a plastic film, an adhesive layer with a thickness of 10μm-50μm and a polarizer.
[0035] Among them, the acrylic acid ester monomer is recorded as (a1), and the bisacrylamide monomer is recorded as (a2).
[0036] The present invention also verifies the performance of the prepared adhesive and polarizer through several embodiments and comparative examples. First, an acrylic copolymer is synthesized.
[0037] Synthesis example 1
[0038] S1. Preparation of mixed monomers
[0039] 80 parts of butyl acrylate, 17 parts of 2-ethylhexyl acrylate and 3 parts of methylenebisacrylamide were mixed uniformly to obtain a mixed monomer;
[0040] S2. Preparation of acrylic copolymer
[0041] Under nitrogen protection, the mixed monomer, 0.24 parts of carbazole-9-dithiobenzyl ester and 150 parts of ethyl acetate were added to the reactor and heated to 70°C, 0.02 parts of azobisisobutyronitrile were added, the reaction was initiated and the temperature was kept for 2 hours; 0.02 parts of initiator were added and the temperature was kept for 2 hours. Finally, 0.02 parts of initiator were added, the temperature was kept for 2 hours, and 150 parts of solvent were added and cooled to obtain an acrylic copolymer solution (A-1).
[0042] In Synthesis Examples 2 to 6, the preparation method is the same as that in Synthesis Example 1. The specific raw materials are shown in Table 1.
[0043] Table 1 Raw materials of acrylic copolymers in Synthesis Examples 1-6 and Comparative Synthesis Examples 1-3
[0044]
[0045] After the acrylic copolymer solution is prepared, it is necessary to measure the weight average molecular weight (Mw) and the number average molecular weight (Mn).
[0046] The weight average molecular weight (Mw) and number average molecular weight (Mn) can be measured by gel permeation chromatography (GPC). The GPC instrument (1260 Infinity II GPC / SEC system) was purchased from Agilent Technologies, where the chromatographic column used a column made of two GRAM polyester copolymer GPC chromatographic columns manufactured by Agilent in series, the eluent was tetrahydrofuran (THF), and the column temperature was controlled at 40°C. In addition, Mn and Mw can be converted using polystyrene (Mw and Mn are known) as a standard substance, and the polydispersity index PDI is obtained by dividing Mw by Mn.
[0047] In each synthesis example and comparative synthesis example, the physical properties of the acrylic copolymer are evaluated as shown in Table 2.
[0048] Table 2 Physical property evaluation table of acrylic copolymers in Synthesis Examples 1-6 and Comparative Synthesis Examples 1-3
[0049]
[0050] It can be seen from Table 1 and Table 2 that the comparative synthesis examples all failed to meet the weight average molecular weight Mw, while the synthesis examples all met it.
[0051] In the present invention, the silane coupling agent used is:
[0052] KBM-103: (phenyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.);
[0053] KBM-503: (γ-methacryloxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.).
[0054] The examples and comparative examples were prepared by using Synthesis Example 1 and a silane coupling agent.
[0055] Example 1
[0056] 0.2 parts of KBM-103 were mixed with 100 parts of the acrylic copolymer obtained in Synthesis Example 1 to prepare an adhesive composition. The obtained adhesive composition was applied to a release film with a thickness of 19 μm in a manner of 20 μm after drying using a knife coater, and dried at 80° C. for 3 min, and then attached to a polarizer, and aged at 23° C. / 50% for 7 days to obtain a polarizer element.
[0057] Examples 2-6, Comparative Examples 1-3
[0058] In Examples 2-6 and Comparative Examples 1-3, the types and amounts of acrylic copolymers and silane coupling agents were changed, and the polarizer element was obtained in the same manner as in Example 1. The specific ingredients are shown in Table 3.
[0059] After the polarizer element is prepared, its performance is tested in the following aspects.
[0060] Adhesion
[0061] The obtained polarizer element was cut into a size of 25 mm wide × 150 mm long to make test strips, and then the adhesion test was carried out according to the national standard GB / T 2792-2014. After the strips were rolled, they were left to stand for 24 hours at 23°C / 50% and then the peel strength was measured by a tensile testing machine (manufactured by Kejian Instrument, KJ-1065A) (peeling angle 180°, peeling speed 300 mm / min). The evaluation criteria are as follows:
[0062] The peel strength is greater than 5N / 25mm and less than 8N / 25mm, which is excellent;
[0063] △: Peel strength is greater than 8N / 25mm, medium;
[0064] The peel strength is less than 5N / 25mm, which is poor.
[0065] Heat and humidity resistance
[0066] Cut the polarizer element in the embodiment or comparative example into a size of 100mm wide × 210mm long, make a test strip, and then bond the strip to the peeling substrate at a pressure of 5kg / cm2, and then degas for 20 minutes under high temperature and high pressure conditions of 50℃ / 0.5MPa to obtain a moisture and heat resistance sample. The bonding must be carried out in a clean room and there must be no bubbles or foreign matter. After the sample is kept at high temperature and high humidity conditions of 85℃ / 85% for 1000h, the moisture and heat resistance is evaluated according to the following criteria:
[0067] No bubbling or warping, excellent;
[0068] △: 1-3 blistering and / or lifting occurred, medium;
[0069] If blistering and / or lifting occurs in 3 or more places, it is poor.
[0070] Trial Period
[0071] The prepared adhesive composition was measured at 25°C using a B-type viscometer (rotor: 3#; rotation speed: 12 rpm; measurement time: 1 min; unit: mPa·s) for the initial viscosity and after 48 hours of placement, and the viscosity change rate of the adhesive composition before and after placement was calculated. The evaluation criteria are as follows:
[0072] The viscosity change is less than 10%, which is excellent;
[0073] △: Viscosity change is greater than 10% and less than 30%, medium;
[0074] The viscosity change is greater than 30%, which is poor.
[0075] The specific test results are shown in Table 3.
[0076] Table 3 Formulation and performance evaluation of the adhesive composition in Examples 1-6 and Comparative Examples 1-3
[0077]
[0078] As shown in Table 3, the comparative examples failed to fully meet the performance evaluations of adhesion, moisture and heat resistance, and trial period, while the embodiments all obtained excellent results, which can solve the problems of poor wettability of the polymer on the surface of the polarizer, the problem of residual glue that is prone to occur during the rework process, and the problem of gelation that is prone to occur during the use of the polarizer.
[0079] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0080] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A hard cross-linked acrylic copolymer, characterized in that: The acrylic copolymer has a weight average molecular weight Mw of 100 to 150w and a polydispersity index PDI of 1 to 4; Including acrylate monomers, bisacrylamide monomers, initiators, chain transfer agents and solvents; When the total weight of the acrylic acid ester monomer and the bisacrylamide monomer is 100 parts, the acrylic acid ester monomer accounts for 80 to 99 parts, and the bisacrylamide monomer accounts for 1 to 20 parts.
2. A hard cross-linked acrylic copolymer according to claim 1, characterized in that: The acrylic acid ester monomer includes at least one of n-butyl acrylate, isobutyl acrylate, n-hexyl acrylate, n-octyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, n-nonyl acrylate, methoxyethyl acrylate, ethoxyethyl acrylate, isooctyl methacrylate, isodecyl methacrylate, lauryl methacrylate and tetradecyl methacrylate.
3. A hard cross-linked acrylic copolymer according to claim 1, characterized in that: The bisacrylamide monomer includes at least one of methylene bisacrylamide, ethylenediamine bisacrylamide, propylenediamine bisacrylamide and butanediamine bisacrylamide.
4. A hard cross-linked acrylic copolymer according to claim 1, characterized in that: The initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, dodecyl peroxide, tert-butyl perbenzoate and tert-butyl pervalerate; the initiator is used in 0.01 to 2 parts by weight.
5. The hard cross-linked acrylic copolymer according to claim 1, characterized in that: The chain transfer agent is selected from at least one of tert-butylbenzocarbodisulfate, carbazole-9-dithiobenzyl ester, 3-benzylsulfonylcarbonylthiosulfonylpropionic acid, 2-phenylethylbenzenedithiol ester, and 2-phenyl-2-propylbenzodisulfide; the chain transfer agent is used in 0.04 to 8 parts by weight.
6. A hard cross-linked acrylic copolymer according to claim 1, characterized in that: The solvent is ethyl acetate, toluene, methyl acetate or acetone.
7. A hard cross-linked acrylic adhesive, characterized in that: The invention is composed of an acrylic copolymer and a silane coupling agent, wherein the acrylic copolymer is any one of the hard-crosslinked acrylic copolymers as described in claims 1 to 6; and the silane coupling agent is used in an amount of 0.01 to 1 part relative to 100 parts of the acrylic copolymer by weight.
8. A hard cross-linked acrylic adhesive according to claim 7, characterized in that: The silane coupling agent is selected from at least one of 3-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane, phenyltrimethoxysilane and vinyltriacetoxysilane.
9. A method for preparing a hard cross-linked acrylic adhesive, for preparing a hard cross-linked acrylic adhesive as claimed in claim 8, characterized in that: The steps include: S1, preparation of mixed monomer: taking a certain amount of acrylic acid ester monomer and bisacrylamide monomer and mixing them evenly to obtain a mixed monomer; S2, preparation of acrylic copolymer: under nitrogen protection, add the mixed monomer, chain transfer agent and solvent in the formula amount into the reactor and heat to 65-70° C., add 1 / 3 of the initiator in the formula amount, initiate the reaction and keep warm for 2-3 hours; add 1 / 3 of the initiator and keep warm for 2-3 hours; finally add the remaining 1 / 3 of the initiator, keep warm for 2-3 hours, add the solvent, cool and discharge, and obtain acrylic copolymer; S3, preparation of adhesive and polarizer element: take acrylic copolymer and silane coupling agent, add solvent to adjust viscosity, apply them on plastic film, and the coating thickness is 10-50μm; after coating, use 75℃-85℃ hot air to dry for 3-5min, stick it on polarizer, and mature it at 23℃ / 50% environment for 7 days to obtain the finished polarizer element.
10. The method for preparing a hard cross-linked acrylic adhesive according to claim 9, characterized in that: The coating method uses a gravure coater, a blade coater or a rotary coater; the plastic film uses a polyethylene terephthalate film that has been stripped and has a thickness of 10 to 100 μm.
Citation Information
Patent Citations
Oil-soluble low-temperature inner-crosslinking-type functional polyacrylate polymer and application thereof
CN110423303A